Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1038/bjc.1997.282
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of etoposide pharmacokinetics after oral etoposide phosphate and oral etoposide

Abstract: Summary Etoposide phosphate is a water-soluble prodrug of etoposide. The plasma pharmacokinetics of etoposide following oral administration of etoposide phosphate or oral etoposide were compared. Seventeen patients with solid tumours were enrolled to receive oral etoposide phosphate 125 mg m-2 on days 1-5 every 3 weeks, with escalation to 175 mg m-2 from course 3 when possible. Patients were randomized to receive oral etoposide phosphate or oral etoposide on day 1 of course 1 and the alternative compound on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Most importantly, phosphate prodrugs are readily cleaved by alkaline phosphatase (ALP), an enzyme widely distributed in plasma and a variety of tissues, to their parent drugs (Fleisher et al, 1985(Fleisher et al, , 1996. This approach has been successfully used for a number of oral and parenterally administered drug candidates on the market (de Jong et al, 1997).…”
mentioning
confidence: 99%
“…Most importantly, phosphate prodrugs are readily cleaved by alkaline phosphatase (ALP), an enzyme widely distributed in plasma and a variety of tissues, to their parent drugs (Fleisher et al, 1985(Fleisher et al, , 1996. This approach has been successfully used for a number of oral and parenterally administered drug candidates on the market (de Jong et al, 1997).…”
mentioning
confidence: 99%
“…However, in a comparative pharmacokinetic study, we found only minor improvement of bioavailability and wide variation in etoposide plasma concentrations (de Jong et al, 1997). In addition, the prodrug was never detectable in plasma after oral administration (de Jong et al, 1997;Sessa et al, 1995). These observations suggested that the prodrug was possibly converted to etoposide within the gastrointestinal lumen.…”
mentioning
confidence: 71%
“…Because this prodrug is considerably more water-soluble, oral administration was expected to result in improved etoposide plasma pharmacokinetics compared with orally administered etoposide. However, in a comparative pharmacokinetic study, we found only minor improvement of bioavailability and wide variation in etoposide plasma concentrations (de Jong et al, 1997). In addition, the prodrug was never detectable in plasma after oral administration (de Jong et al, 1997;Sessa et al, 1995).…”
mentioning
confidence: 71%
“…Importantly, phosphate prodrugs are cleaved in the intestine and generate a super-saturated parent solution that enhances the absorption flux (Heimbach et al, 2003a). On the other hand, poor phosphate cleavage can give rise to an unacceptable oral profile, low parent drug exposure, and a lack of improvement in clinical efficacy (de Jong et al, 1997;Heimbach et al, 2003a;Stella, 2010). Poorly soluble parents with sufficient solubility in the formulation vehicle, and dissolution times less than their gastrointestinal transit times will exhibit slow yet complete absorption and in these cases a phosphate prodrug may not be beneficial (Heimbach et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a soluble prodrug approach is generally considered for the purpose of enhancing exposures. Phosphate prodrugs are an effective and commonly used approach to overcome solubility issues in drug delivery and have successfully been used for a number of oral and parenterally administered marketed drugs (Fleisher et al, 1996;de Jong et al, 1997;Heimbach et al, 2003a;Rautio et al, 2008;Jana et al, 2010;Stella, 2010;Huttunen et al, 2011). The advantages of phosphate prodrugs include their chemical stability, several orders of magnitude of improved solubility as compared with parent, and relative ease of synthesis in the presence of a suitable handle (Heimbach et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%